The sound imitation of some national instruments in piano music - V. Karkina, Svetlana (2018)
The article reveals the textural, timbre-dynamic, harmonic, performing and other musical means of imitating the sound of national instruments in piano music. Based on the analysis of literature and works by M. Mussorgsky, S. Rachmaninov, F. Liszt, Wang Jiangzhong, Zhu Wanhua, A. Rudenko, R. Kasimov and other composers, summarizing the performing and pedagogical experience of studying piano works shows the means of implementing various instruments to groups of idiophones, membranophones, chordophones and aerophones according to the instrumental classification of Hornbostel-Sachs. The article shows that onomatopoeia is based not only on the sound image of the primary source instrument, but also on recreating the playing techniques of playing it. At the same time, the traditions of academic art, the achievements of European pianism and the sound capabilities of the piano are actualized. Imitation of the sound of the bell, one of the idiophones, occupies an important place in foreign and domestic music. In the works of Russian composers, various types of Orthodox bells ring out, such as Blagovest, Perebor, Perezvon, and Trezvon. In the works of Chinese composers, the sounds of ancient bianzhong ceremonial bells are displayed. The imitation of a bell is based on the reproduction of its timbre-acoustic characteristics, rich in overtones of a booming sound, long and smoothly dying out, accompanied by other harmonies or figurations, pedalization of the piano. The imitation of string-stringed chordophones is notable for its expressiveness, melodic expressiveness, improvisation, and rich ornamentation. Piano playback of plucked chordophones of the zither type is based on the use of arpeggiated figures, pizzicato, vibrato, glissando, etc. wind themes are distinguished by an abundance of melisms (trillare, acciaccatura, glissando, repetitio). The imitation of membranophones is carried out by ostinate rhythmic formulas, specific timbres. Imitation of instruments on the piano reveals the rich timbre and coloristic potential of the piano, creates a special national flavor of the work, reflects the originality of ethnic musical traditions and the originality of their artistic representation.